A autoanálise de coordenadores pedagógicos sobre sua atuação como formadores de professores - Pereira, Rodnei (2010)
The training of teachers like responsability of pedagogical coordinator is presented as a trend that slowly is being built by publics politics aimed at professionals in this area, such as Programa Ler e Escrever, for the inicial terms of elementary school of state public network of Sao Paulo, and that was basis of consideration of this work. The research aimed to analyze how teachers pedagogical coordinators of the state of São Paulo understand and describe their role as trainers of teachers. For various reasons, we chose six participants who worked in elementary schools of a single Diretoria Regional de Ensino, located in the east of the Capital. In this study, we used like procedure to collect information interviews, discourse analysis which sought grounds in qualitative research methodology. The results indicated that the work of teachers pedagogical coordinators has elements of bureaucratization and inspection of teaching, which marked the history of their profession. The efforts of participantes to develop the teachers continuing education are the result of conquests undertaken individually and marked by subjective interpretations on this task, that find explanation in the distortions between the formulation of continuity educational politics and the objective conditions work of those professionals